ANALISIS PENGARUH MANAJEMEN LABA TERHADAP PROFITABILITAS PERUSAHAAN DENGAN GOOD CORPORATE GOVERNANCE SEBAGAI VARIABEL MODERASI: STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2010-2012 - Salim, Hasan (Jurnal Manajemen, 2015)
The aims of this study is to analyze the effect of earning management on the profitability of the company moderated by good corporate governance. The measurement method of earning management employed is discretionary revenueÂ approach that applies the method of conditional revenue developed by Stubben (2010). Good corporate governance is measured by frequency of audit committee meetings. Companyâs profitability is measured by using Return on Assets ratio (ROA). The total sample for this study are 70 manufacturing firms listed in Indonesia Stock Exchange from 2010-2012. The method used for data analysis is multiple regression. The result of this study shows that earning management influences companyâs profitability. Moreover, good corporate governance is the moderator of the relationship between earning management and companyâs profitability.Â Keywords: good corporate governance, earning management, conditional revenue model,Â audit committee, profitability